(untitled) (Research, Society and Development, 2022)
Educational policy fits into the type of majority policy, in which the government has the responsibility and competence to offer all Brazilians basic education, with access, permanence and quality, and is part of the constitutional rights of the Brazilian citizen in article 5 of the Constitution. Federal of 1988. Public education has its own legislation, which determines guidelines, functions and their functioning: LDB No. 9,394/1996, together with the PNE, Law No. Brazilian education for a determined period of one decade. Teacher training is a public policy that seeks to respond to the qualification of public education and overcome the challenges that permeate school contexts, a fact that compromises student learning, in addition to promoting professional appreciation for teachers. The article expresses the correspondence of the objectives established in the Program for Continuing Education of Teachers of Early Childhood Education, carried out by the municipal public network of Fortaleza from 2017 to 2018, investigating the results obtained according to the narratives of the researched subjects. The continuing education program in 2017 aimed to re-elaborate the pedagogical proposal of municipal public institutions in Fortaleza. In 2018, the objective was to strengthen the early childhood education curriculum, with the pedagogy of projects, to promote the learning rights of children established in the BNCC (Brazil, 2017). The research was carried out in school units in District 3, from September to November 2020. The target audience were teachers, pedagogical coordinators and technical-trainers working in the early childhood education stage, pre-school segment. The researched literature used documents relevant to public education in the following spheres: national, state and municipal. According to the narratives of the subjects, it was possible to conclude that, in 2017, the proposed objective was reached in its entirety, but in 2018, it was not possible to achieve full success, due to the factors that involve the conceptions and knowledge within the scope of the curriculum. of early childhood education.